Accounting System for MSME Development - Noviani Noviani; Heriyati Chrisna; Hernawaty Hernawaty (Proceeding of The International Conference on Economics and Business, 2023)
This study aims to provide input to MSMEs in the village of Klambir Lima Kebun Deli Serdang. Regarding the importance of using an accounting system and making work much easier and smoother. This study uses qualitative data with conducted secondary data and primary data taken from Klambir Lima Kebun Village. Research result it is hoped that it can be utilized for use in MSMEs. The results of this research describing the easiest system for Klambir five village SMEs is HUI POST which is the easiest to apply by Kelambir Lima MSMEs users, especially Loundri businesses.